Dual energy X-ray absorptiometry: Pitfalls in measurement and interpretation of bone mineral density - Garg, M. K. (Medknow Publications & Media Pvt Ltd, 2013)
Osteoporosis is common disorder of elderly population all over the world as well as in India. The presence of osteoporosis predicts fracture risk. Fragility fracture has marked morbidity as well as mortality. Thus, osteoporosis has marked therapeutic and economic implications. Osteoporosis is defined by low bone mineral density (BMD). The gold-standard method to assess BMD is dual X-ray absorptiometry (DXA). In India, hologic and lunar machines are most commonly used to measure BMD; these machines have their own normative data from which patients BMD is compared and results are generated. As per recommendations, all postmenopausal women and men above 70 years need BMD estimation other than quite a few other specific indications as well. With increasing life expectancy, increased awareness of osteoporosis, and availability of DXA machines, there is flooding of requests for BMD estimation. In view of all this, it becomes imperative on part of physicians, orthopedicians, rheumatologists, and endocrinologists alike to be fully aware about pitfalls in BMD assessment by DXA and interpretation of BMD reports.